Reading in changing society - Lauristin, Marju; Vihalemm, Peeter (2014)
The changing state of reading and its fate in the digitalised world is one of the core issues in the contemporary debates about the future of culture. The central position of the printed word, and primarily, books as the most valuable cultural medium and the main source of knowledge, are becoming questioned in the age of the Internet. Reading as gateway to the world of fantasies has been challenged by powerful audiovisual media. Is the pleasure of reading as a creative process involving imagination and self-cognition disappearing, and being replaced by the quick exchange of impressions and images in social media? Are these critical notes and concerns about the future of reading just rapid generalisations and misunderstandings, evoked by the invasion of new technologies in the old and well-established world of books? The articles gathered here represent empirical studies, theoretical and historical reflections on the changes in the world of books and reading in the Baltic and Nordic countries, as well as descriptions of the new library practices that reflect the creative efforts to adapt to the changing social and technological environment.